Turning Points in the Chinese Civil War: A Financial Market Perspective. (4th November 2018) - Howell, Anthony; Zhao, Liuyan
Abstract : This paper provides a quantitative assessment of contemporary beliefs about 'turning points' that shaped the outcome of the Chinese Civil War (1946–49). We employ an endogenous structural break method relying on a novel data set to exploit breakpoints in the daily price quotes of Chinese sovereign bonds traded on the London market. As late as spring 1947, the London market evidently believed there was a reasonable chance of either the Kuomintang Party winning the war or alternatively achieving a peace agreement. The timing of our major breakpoints generally correspond with the dates of well‐known events deemed as important turning points. Caveats exist, however. In particular, some events – for example the Liu‐Deng expedition – stand out where we observe stark contrasts between the perceptions held by contemporaries and historians.